A Theological Analysis of Biological Determinism Claims in the Context of Epigenetics and Brain Plasticity - Seyithan Can (Darulfunun Ilahiyat)
Several theoretical studies have investigated biological determinism. First, it leaves no room for divine intervention in the various spheres of human activity. Second, it asserts that heredity significantly influences human behavior. This notion emphasizes the idea that humans possess both freedom and wildness. According to biological determinism, behavior is predetermined by DNA, reducing physiological brain activity. Consequently, what is commonly perceived to be human freedom is illusory. If an individual’s actions are not a result of their own will, the issue of justice arises from the rewards and punishments that God metes out in response to human behavior. To address the theological dilemmas posed by these assertions of biological determinism, we sought to ground human freedom, will, and responsibility within the framework of God’s justice, by drawing on insights from epigenetics and brain plasticity. However, can recent developments in genetic science comprehensively elucidate human behavior, potentially revealing the freedom we once believed we possessed to be an illusion? Answering this question was one of the primary objectives of this study.